PRCI trade flow analysis training: Lecture 5: Evaluating changes in agri food demand in Papua New Guinea over time: Learning about the BACI trade dataset - Schmidt, Emily; Fang, Peixun; Thammachote, Pasakorn; Babu, Suresh Chandra; Diao, Xinshen (Michigan State University, 2021)
Trade flow among the countries determines the economic benefits countries gain from trade. For many Asian developing countries, agricultural and food trade is an important engine for agricultural growth. The ability to use trade flow data for analyses is important for decision making related to trade policies. The training is going to be organized through a set of virtual workshop sessions. In order to prepare for the training and maximize the benefits from the online training workshop, participants are expected to read the workshop materials and get familiar with the trade datasets shared in advance.